Analyzing Errors in Lesson Plans of Arabic Teacher Professional Education Participants During the Teaching Practise at Schools - Moh. Ainin; Mohammad Ahsanuddin; Irhamni Irhamni; Muhammad Lukman Arifianto; Moch. Wahib Dariyadi; Faishol Mahmud Adam Ibrahim (Universitas Islam Negeri Palangka Raya, 2021)
One of the government